IDENTIFIKASI PERUBAHAN TUTUPAN LAHAN DI KEBUN RAYA MEGAWATI SOEKARNOPUTRI MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Wuisan, Imanuel O.; Saroinsong, Fabiola Baby; Langi, Martina A. (AGRI-SOSIOEKONOMI, 2022)
This study aims to identify land cover and analyze land cover changes in the Megawati Soekarnoputri Botanical Gardens area in 2010-2019. This research was conducted in December 2021-January 2022 at the Megawati Soekarnoputri Botanical Gardens, Southeast Minahasa and at the Forestry Science Study Program, Faculty of Agriculture, Sam Ratulangi University, Manado. This study uses satellite image/ Digital Globe Imagery with visual interpretation methods or on-screen digitization. The results showed that there were 6 land cover classes: forest, developed, open land, agriculture, shrub, and water bodies. The land cover area resulting from the interpretation of satellite image in 2010 is 189,51 Ha of forest, 0,34 Ha of developed, 6,78 Ha of open land, 9,71 Ha of agriculture, 8,96 Ha of shrub and water bodies of 6,11 Ha. The land cover area from the interpretation of satellite photos in 2019 is 185,79 Ha of forest, 0,57 Ha of developed, 6,02 Ha of open land, 12,40 Ha of agriculture, 8,71 Ha of shrub and water body 4,62 Ha. The results of the analysis of land cover changes showed that forested land cover from 2010 to 2019 in Megawati Soekarnoputri Botanical Gardens decreased by (0.22%), namely 0,22 Ha, so that forested land cover in 2019 had an area of 189,10 Ha and non-forest land cover 32,31 Ha.